1999
DOI: 10.1016/s0014-5793(99)01580-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for glucose and sorbitol‐induced nuclear export of glucokinase regulatory protein in hepatocytes

Abstract: Glucokinase is rapidly exported from the nucleus of hepatocytes in response to a rise in glucose or fructose 1-P. We demonstrate using confocal microscopy and quantitative imaging that in contrast to previous findings, the regulatory protein of glucokinase (GKRP) also translocates from the nucleus during substrate-induced translocation of glucokinase. However, the fractional decrease in nuclear GKRP is smaller than for glucokinase and is determined by the metabolic state and not by the distribution of glucokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 23 publications
7
51
0
Order By: Relevance
“…Based on this observation and the structural information, it is possible that the glucose and compound A have additive effects in changing GK structure to a more active form that precludes its association with GKRP. It has been reported that inactive GK is localized in the nucleus as a complex with GKRP in hepatocytes and that GK is released from the complex to the cytoplasm when the glucose concentration is elevated (19). We observed that treatment with compound A at a low glucose concentration enhanced the translocation of GK from the nucleus to the cytoplasm in both primary cultured rat hepatocytes and in rat liver tissue.…”
Section: Discussionmentioning
confidence: 47%
“…Based on this observation and the structural information, it is possible that the glucose and compound A have additive effects in changing GK structure to a more active form that precludes its association with GKRP. It has been reported that inactive GK is localized in the nucleus as a complex with GKRP in hepatocytes and that GK is released from the complex to the cytoplasm when the glucose concentration is elevated (19). We observed that treatment with compound A at a low glucose concentration enhanced the translocation of GK from the nucleus to the cytoplasm in both primary cultured rat hepatocytes and in rat liver tissue.…”
Section: Discussionmentioning
confidence: 47%
“…The finding that the GK activators caused dissociation of bound GK and translocation to the cytoplasm appeared incongruous with the size exclusion data showing that GKA1 does not dissociate GK from GKRP. High glucose concentration and glucose analogs that are not metabolized by GK to a significant extent (5-thioglucose and mannoheptulose) also cause translocation of GK from the nucleus (18,27,36). It has been generally assumed that the translocation induced by glucose is due to dissociation of GK from GKRP.…”
Section: Discussionmentioning
confidence: 99%
“…We propose the following hypothesis to account for these observations. Translocation of GK from the nucleus to the cytoplasm may require two complementary mechanisms: release of GK from GKRP, which is localized predominantly but not exclusively in the nucleus (18,27), and transfer to another GK receptor that is localized predominantly in the cytoplasm (3). Various GK binding proteins have been identified by the yeast two-hybrid system (40 -42) or by random peptide library screening (41), which are potential candidates for the cytoplasmic receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations